Maternal Undernutrition and Fetal Developmental Programming of Obesity: The Glucocorticoid Connection. (February 2015) - Correia-Branco, Ana; Keating, Elisa; Martel, Fátima
An adequate maternal nutrition during pregnancy is crucial for the health outcome of offspring in adulthood. Maternal undernutrition during critical periods of fetal development can program the fetus for metabolic syndrome (MetS) later in life, especially when postnatally challenged with a hypernutritive diet. Adipogenesis, which begins in utero and accelerates in neonatal life, is a major candidate for developmental programming. During fetal development, the hypothalamic–pituitary–adrenal (HPA) axis is extremely susceptible to programming, and the HPA tone is increased throughout life in undernourished conditions. As a consequence, an alteration in the expression and function of glucocorticoid (GC) receptors and of the major GC regulatory enzymes (11β-hydroxysteroid dehydrogenase 1 and -2) occurs. In this review, we will give insights into the role of maternoplacental adverse interactions under the specific context of maternal undernutrition, for later-in-life MetS development, with a special emphasis on the role of GCs.